2019
DOI: 10.1108/bepam-01-2019-0001
|View full text |Cite
|
Sign up to set email alerts
|

Factors that trigger bullying amongst subcontractors toward intention to quit in the construction projects

Abstract: Purpose The purpose of this paper is to examine the relationships between three key factors that cause workplace bullying among subcontractor managers toward intention to quit the undertaken project within the context of Malaysia. Design/methodology/approach This study utilized the simple sampling method to select its study sample, while the questionnaire survey approach was implemented amidst 500 G6 and G7 contractor managers across Peninsular Malaysia. A total of 210 completed questionnaires were returned.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
1
1
0
Order By: Relevance
“…According to the accepted hypothesis, job stress affects the intention to leave the NPE company significantly. These findings are consistent with various previous research that job stress affects employees' intention to leave the workplace (Hussain and Xian, 2019); (Jalali et al, 2019); (Thorsteinsson et al, 2014). Additionally, job stress is closely associated with the intention to quit working, which aligns with (Qureshi et al, 2013), who discovered that workplace stress increases the likelihood of employees quitting their jobs.…”
Section: Figure 2 the Results Of The Hypothesis Testingsupporting
confidence: 92%
See 1 more Smart Citation
“…According to the accepted hypothesis, job stress affects the intention to leave the NPE company significantly. These findings are consistent with various previous research that job stress affects employees' intention to leave the workplace (Hussain and Xian, 2019); (Jalali et al, 2019); (Thorsteinsson et al, 2014). Additionally, job stress is closely associated with the intention to quit working, which aligns with (Qureshi et al, 2013), who discovered that workplace stress increases the likelihood of employees quitting their jobs.…”
Section: Figure 2 the Results Of The Hypothesis Testingsupporting
confidence: 92%
“…In the previous research, not many respondents were taken from energy companies with very different characters from the various companies that were the subject of previous research. There is research that raises the subject in industrial work environments, especially construction, which shows that employees experience job stress which increases the intensity of quitting work (Jalali et al 2019;Sun, 2011) added that bullying between employees increases the intention to quit working. However, (M. I.…”
Section: Introductionmentioning
confidence: 99%
“…Our first hypothesis describes how workplace bullying affects employees' intent to leave, consistent with prior research by Naseer and Khan (2015) and Najam et al (2018). The study's findings revealed a significant link between workplace bullying and emotional exhaustion, in line with a previous study (Jalali, Hidzir, Jaafar, and Dahalan, (2019). The study results also suggest that emotional exhaustion leads to the intention to leave; therefore, our third hypothesis is consistent with the results (Srivastava & Agarwal, 2020, Arici, 2018.…”
Section: Conclusion and Discussionsupporting
confidence: 91%
“…This finding, however, contradicted previous findings on the role of government in encouraging the participation of the youth in agropreneurship. Previous studies showed that the role of the government is significant in promoting agropreneurship [46,49,[75][76][77][78][79]. However, it is insignificant when it comes to supporting entrepreneurial practices.…”
Section: Discussionmentioning
confidence: 99%